Pancreatic Steatosis: What Should Gastroenterologists Know? - Prachayakul, Varayu; Aswakul, Pitulak (JOP. Journal of the Pancreas, 2015)
When hyperechoic pancreatic parenchyma is observed on endoscopic or transabdominal ultrasound, fat infiltration of the pancreas is suspected. This condition was first reported by Ogilvie in 1993 and is termed fatty pancreas, pancreatic lipomatosis, non-alcoholic fatty pancreas, or pancreatic steatosis. Diagnosis of this condition mostly relies on imaging tools such as magnetic resonance imaging, computed tomography, or ultrasonography rather than histology. Although the condition is rare, it has clinical significance. There are multiple hypotheses regarded the etiology of this condition, listing factors such as viral infections, toxins, and congenital syndromes as possible causes. Metabolic syndrome and diabetes mellitus correlated with this condition. However, other etiologies should also be considered to aid specific treatment. In addition to a correlation between pancreatic steatosis and metabolic syndrome, relationships between pancreatic steatosis and worsened severity and prognosis of pancreatic cancer, increased complications after pancreatic surgery, and acute pancreatitis were reported. Gastroenterologists should be well informed about this condition for better care of these patients. Image: Siriraj Hospital. Bangkok, Thailand.